Diplomatic Protection in International Law: A Comprehensive Analysis of ICJ Rulings with Particular Focus on the Landmark Diallo Case Judgment of 2012 - Diallo, Boubacar Sidi (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2024)
This paper explores the concept of diplomatic protection in international law through a detailed analysis of International Court of Justice (ICJ) rulings, with a particular focus on the landmark June 19, 2012 judgment in Ahmadou Sadio Diallo (Republic of Guinea v. Democratic Republic of the Congo). Diplomatic protection, a traditional legal mechanism allowing states to seek redress for their nationals harmed by other states, reflects a nuanced intersection between state sovereignty and individual rights within international law. This study traces the evolution of diplomatic protection in ICJ jurisprudence, assessing how the Court has balanced state responsibility with the protection of individuals abroad. The Diallo judgment is analyzed for its substantive contributions, particularly in recognizing non-material damages and the principles underpinning adequate reparations. Through this case study, the paper examines key requirements for diplomatic protection, such as nationality, exhaustion of local remedies, and the discretionary nature of state action. By evaluating the im plications of this and related ICJ rulings, this research offers insights into the evolving role of diplomatic protection and its effectiveness in modern international law for advancing individual justice within the framework of state sovereignty.